Democratic Republic of Congo Urbanization Review : Productive and Inclusive Cities for an Emerging Congo - World Bank (Washington, DC: World Bank, 2017)
The Democratic Republic of Congo has the third largest urban population in sub-Saharan Africa (estimated at 43% in 2016) after South Africa and Nigeria. It is expected to grow at a rate of 4.1% per year, which corresponds to an additional 1 million residents moving to cities every year. If this trend continues, the urban population could double in just 15 years. Thus, with a population of 12 million and a growth rate of 5.1% per year, Kinshasa is poised to become the most populous city in Africa by 2030. Such strong urban growth comes with two main challenges – the need to make cities livable and inclusive by meeting the high demand for social services, infrastructure, education, health, and other basic services; and the need to make cities more productive by addressing the lack of concentrated economic activity. The Urbanization Review of the Democratic Republic of Congo argues that the country is urbanizing at different rates and identifies five regions (East, South, Central, West and Congo Basin) that present specific challenges and opportunities. The Urbanization Review proposes policy options based on three sets of instruments, known as the three 'I's – Institutions, Infrastructures and Interventions – to help each region respond to its specific needs while reaping the benefits of economic agglomeration The Democratic Republic of the Congo is at a crossroads. The recent decline in commodity prices could constitute an opportunity for the country to diversify its economy and invest in the manufacturing sector. Now is an opportune time for Congolese decision-makers to invest in cities that can lead the country's structural transformation and facilitate greater integration with African and global markets. Such action would position the country well on the path to emergence.